2020
DOI: 10.31234/osf.io/8pvqy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Back-off: Evaluation of Robot Motion Strategies to Facilitate Human-Robot Spatial Interaction

Abstract: Standstill behavior by a robot is deemed to be ineffective and inefficient to convey a robot’s intention to yield priority to another party in spatial interaction. Instead, robots could convey their intention and, thus, their next action via motion. We developed a back-off movement to communicate the intention of yielding priority to pedestrians at bottlenecks. To evaluate human sensory perception and subjective legibility, the back-off is compared to three other motion strategies in a video study with N = 167… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This underlines a major motivation for this research: robots should be designed for comprehension in order to engender trust. Kauppinen et al validated the relationship between trust and comprehension with the Human Computer Trust Rating Scale, which was tested with air traffic control systems [27]. We have demonstrated this relationship in robot yielding cues.…”
Section: Discussionmentioning
confidence: 63%
“…This underlines a major motivation for this research: robots should be designed for comprehension in order to engender trust. Kauppinen et al validated the relationship between trust and comprehension with the Human Computer Trust Rating Scale, which was tested with air traffic control systems [27]. We have demonstrated this relationship in robot yielding cues.…”
Section: Discussionmentioning
confidence: 63%
“…Many people would pass by the robot without helping, even if they may have understood it to be stuck (Figure 6). While improved communication design through lights and dynamic displays [30,31,39], sounds to engender empathy [28], or movement to signal intent [29,32,33] may improve communications and interaction with some people, it is also possible that some members of the public will not engage with the robots or will be actively antagonistic towards them. Such behaviors are evidenced by the incident reports provided after the pilot.…”
Section: Discussionmentioning
confidence: 99%
“…Their review of prior studies found that LED light strips may not be entirely interpretable without prior training on what the signals mean [30] and that gaze may be a more understandable signal in communicating a robot's trajectory [31]. Angelopulos et al motivate their study based on prior work with non-humanoid robots where people did not always interpret strategies such as backing off [32] or moving out of the way [33] correctly and so they proposed the use of deictic arm gestures to increase interpretability [29]. Their findings show that such arm gestures were better at conveying the path a robot would take as opposed to adjusting the robot's gaze alone.…”
Section: Human-robot Communication In Publicmentioning
confidence: 99%